(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2022)
Introduction: At the University of Toledo College of Medicine and Life Sciences, 3rd year medical students experience the field of neurology through a 5-week clerkship and rotate through different inpatient services along with outpatient clinics. Students receive didactic lectures from senior faculty members prior to clinic about various neurological topics to supplement their in-clinic learning. Students also receive clinical setting-based teaching through the residents they work with. In this research project, we focus on the impact of resident led inpatient lectures on clinical knowledge and management of seizures. Methods: 3rd year medical students rotating on the neurology clerkship at University of Toledo were divided into two groups - if they received a resident-led didactic lecture or not. They were then given an online link to an optional anonymous survey. Students rated their perceived competency on a Likert scale of “strongly agree (high score)” to “strongly disagree (low score)” on how to clinically identify seizures or epilepsy and initial management. Additionally, students were given several examples of seizure management and using the same scale, asked if they agreed or disagreed. Results: 3rd year medical students who received the resident-led didactic lecture on seizure and epilepsy clinical application and initial management scored higher on average on the survey, with statistical significance (p<0.05) seen when asked to clinically identify a seizure and how to record a seizure event in the hospital setting. Discussion: Resident-led didactic lectures in the hospital setting can provide an additional educational tool to 3rd year medical students on their neurology rotation. This may be helpful for students to link their classroom-based knowledge to clinical application towards seizure and epilepsy patients on the wards.